KEPUTUSAN PAPUA NUGINI DALAM KERJASAMA BILATERAL PNG SOLUTION DENGAN AUSTRALIA - Mahadewi, I. A. A Wulansari; Dewi, Putu Ratih Kumala; Surya, A. A. Bagus (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT This research analyzes the rationale of Papua New Guinea’ decision to collaborate with Australia in PNG Solution policy, that has drawn a considerable amount of critiques. This research adopted the qualitative method, and aimed at interpreting distinctive feature of PNG Solution based on emerging facts. In addition, the secondary data generated for this research is obtained from literature review as well as online research. Furthermore, this topic is selected based on the fact that Papua New Guinea withdrawal from its commitment to ‘seven reservations’, which is initially submitted by Papua New Guinea itself in order to ratify the 1951’s Refugee Convention. Thus, according to the result of this research, it is indicated that Papua New Guinea’ visions and missions in Alotau Accord 2012 is paralleled to the benefit gained from PNG Solution. Additionally, this particular decision also correspond with two concepts Rational Actor Model and National Interest, which has been adopted for this research, and therefore is a rational decision based on Rational Choice Theory. Keywords : asylum seeker, PNG Solution, Papua New Guinea, Australia, rational choice theory